Nanosized niobium (V) and tantalum (V) oxide ceramics as competitive oxidizers within aluminium-based nanothermites - Pierre Gibot; Franck Oudot; Bastien Lallemand; Fabien Schnell; Denis Spitzer (Energetic Materials Frontiers, 2021)
Among the energetic mixtures, one category are thermites. Thermites are highly reactive composites described as consisting of a fuel (metal) and an oxidizer (metal oxide) at micron scale. The use of nano-sized reactants, with higher surface area to volume ratio than micron-sized counterparts, considerably increases reactive properties and consequently raises their interest. The present work expands on this aspect by investigating two thermites mixtures, nano-aluminium (Al) with niobium (V) and tantalum (V) oxides. These oxidizers were selected based on their weak reactive character at micron-scale. The reactants and their respective derived energetic nanocomposites were characterized by X-ray diffraction, scanning electron microscopy coupled to energy dispersive scattering, nitrogen sorption, and energetic performance (sensitivity, combustion reaction). The reactive properties of both energetic systems were evidenced due to the nanostructuring of the two transitional metal oxides. The use of Nb2O5 and Ta2O5 as oxidizers in gasless nanothermites is demonstrated for the first time.